2005
DOI: 10.1177/1050651904272978
|View full text |Cite
|
Sign up to set email alerts
|

The Computer Expert in Mixed-Gendered Collaborative Writing Groups

Abstract: When mixed-gendered student teams collaborate on technical writing tasks, a single male often emerges as the group computer expert. The effects of this trend on perceptions of workload are unknown. This article reports the results of a study in which 12 mixed-gendered teams answered questionnaires on the division and perceptions of labor in their teams. Detailed case studies of four teams supplement the questionnaires. Findings suggest that computer work was highly visible, highly valued, and dominated by men.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 11 publications
4
14
1
Order By: Relevance
“…Many women told us that their male peers gave their ideas less credit and failed to trust them with technical work on group projects, a finding consistent with Meadows and Sekaquaptewa (2013), Wolfe and Alexander (2005), Natishan, Schmidt and Mead (2000) and others. This lack of trust translated into a lack of learning opportunities and students who had been excluded from work on a project found their performance suffering when they failed to master the content a project was supposed to teach.…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…Many women told us that their male peers gave their ideas less credit and failed to trust them with technical work on group projects, a finding consistent with Meadows and Sekaquaptewa (2013), Wolfe and Alexander (2005), Natishan, Schmidt and Mead (2000) and others. This lack of trust translated into a lack of learning opportunities and students who had been excluded from work on a project found their performance suffering when they failed to master the content a project was supposed to teach.…”
Section: Resultssupporting
confidence: 66%
“…This unequal distribution of labor was correlated with self-perceptions of learning: students who presented technical slides and students who answered more questions perceived themselves as learning more during the presentation. These findings mirror those of other, smaller-scale studies that likewise found male students disproportionately assumed technical roles in projects while female students were more likely to complete writing and organizational work (Natashan, Schmidt & Mead, 2000;Wolfe & Alexander, 2005). …”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…Consistent with other research [4][5][6], the women in the projects observed here completed a disproportionate amount of the writing for their teams. In their final interviews, students described secretarial work as including minutestaking, revising documents, and often drafting documents.…”
Section: Observation 5: the Invisibility Of Writing Disproportionatelsupporting
confidence: 89%
“…These studies have helped illustrate common problems such as the tendency of student teams to arrive at consensus prematurely [1,2], over-emphasis on efficiency at the expense of understanding [3], gender stereotyping of women into clerical roles and men into technical roles [4][5][6], and a tendency for students with poor leadership skills to grab the reigns of projects [2]. This paper adds to this research base by elucidating how engineering students' avoidance and dismissal of written communication contributes to many of the major problems experienced in student teams.…”
Section: Introductionmentioning
confidence: 99%